Fluence-based dosimetry of proton and heavier ion beams using single track detectors. (13th January 2016) - Klimpki, G; Mescher, H; Akselrod, M S; Jäkel, O; Greilich, S
Abstract: Due to their superior spatial resolution, small and biocompatible fluorescent nuclear track detectors (FNTDs) open up the possibility of characterizing swift heavy charged particle fields on a single track level. Permanently stored spectroscopic information such as energy deposition and particle field composition is of particular importance in heavy ion radiotherapy, since radiation quality is one of the decisive predictors for clinical outcome. Findings presented within this paper aim towards single track reconstruction and fluence-based dosimetry of proton and heavier ion fields. Three-dimensional information on individual ion trajectories through the detector volume is obtained using fully automated image processing software. Angular distributions of multidirectional fields can be measured accurately within ±2° uncertainty. This translates into less than 5% overall fluence deviation from the chosen irradiation reference. The combination of single ion tracking with an improved energy loss calibration curve based on 90 FNTD irradiations with protons as well as helium, carbon and oxygen ions enables spectroscopic analysis of a detector irradiated in Bragg peak proximity of a 270 MeV u −1 carbon ion field. Fluence-based dosimetry results agree with treatment planning software reference.